Influence of Interleukin IL-2 and IL-12 + IL-18 on Surface Expression of Immunoglobulin-Like Receptors KIR2DL1, KIR2DL2, and KIR3DL2 in Natural Killer Cells - Slawomir Chrul; Ewa Polakowska; Agnieszka Szadkowska; Jerzy Bodalski (Mediators of Inflammation)
Natural killer (NK) cells express killer cell inhibitory receptors (KIRs) that recognize polymorphic class I MHC molecules. In the present study, we analyze the modulatory effect of IL-2 alone or a combination of IL-12 with IL-18 on surface expression of killer cell immunoglobulin-like receptors KIR2DL1, KIR2DL2, and KIR3DL2 in NK cells. Thus, it was found that IL-2 causes a significant increase in the proportion of cells with given studied receptors. Stimulation by a mixture of IL-12 and IL-18 caused significant increase in the fraction of cells with the KIR2DL1 and KIR2DL2, however no significant change in the percentage of cells with KIR3DL2 receptor on their surface was observed. The results of the study show the presence of KIRs on both resting and activated NK cells, this may suggest that KIRs have also an important role in the regulatory processes after activation of this subpopulation of cells.